Changes in Protein Level in the Cerebrospinal Fluid of a Patient with Cerebral Radiation Necrosis Treated with Bevacizumab. (January 2014) - Yano, Hirohito; Nakayama, Noriyuki; Morimitsu, Kasumi; Futamura, Manabu; Ohe, Naoyuki; Miwa, Kazuhiro; Shinoda, Jun; Iwama, Toru
A 32-year-old woman underwent surgeries and radiation therapy for astrocytoma. She developed symptomatic radiation necrosis in the lesion, which caused hydrocephalus. She initially underwent ventricular drainage, because the protein level in the cerebrospinal fluid (CSF) was 787 mg/dL, which was too high for shunt surgery. Because she also had breast cancer, which was pathologically diagnosed as an invasive ductal carcinoma, standard bevacizumab therapy in combination with paclitaxel every 2 weeks was selected. Interestingly, after 2 days, the agents had dramatically reduced the CSF protein level. However, it returned to approximately the initial level within 2 weeks. After two courses of this regimen, a ventriculoperitoneal shunt was placed. After 10 courses of this regimen, the CSF protein level decreased to 338 mg/dL, which is less than half of the initial level. Long-term administration of bevacizumab might decrease leakage of protein from the vessels around the ventriculus.